Aplikasi Pendaftaran Peserta Didik Baru Berbasis Web dengan Metode Waterfall pada TKS Khalifah - Asqia, Misna; Aziz, Raihan Daffa (LPPM STT Terpadu Nurul Fikri, 2025)
The development of information technology has encouraged educational institutions to adopt more efficient systems in managing administrative processes, including the admission of new students. TKS Khalifah currently faces problems in the registration process which is still done manually, causing inefficiency and potential data errors. This study aims to design and build a new student registration website using the Laravel framework with the Waterfall method. This system is expected to help address existing problems by facilitating the digital management of prospective student data. The testing methods used include black box testing and User Acceptance Testing (UAT) to ensure the functionality and quality of the system. The results of the study indicate that the developed system successfully meets user needs and increases the efficiency of the registration process at TKS Khalifah. Further development of additional features, further testing with other methods, and long-term evaluation are recommended for future research to ensure system sustainability and stability.